Urgensi Tauhid dalam Membangun Epistemologi Islam - Bambang Irawan (TSAQAFAH, 2011)
The reform efforts undertaken by contemporary Muslim thinkers have so far not been able to alter significantly the presence of Muslim which seems in the shadow of western progress in the context of science. This condition is due to the effect of undermining of Western thought through their epistemology packaging. Of course, we cannot blame the West as they have their own paradigm which is different with the Islamic paradigm in developing knowledge. Accordingly, the questions arise: why Muslim scholars are not working hard to build an epistemology that carries the message of monotheism; why they are hurry to accept the truth of Western epistemology without a fundamental review on revelation, so they become loyal followers of Western theories and concepts. Thus, the greatest challenge for Muslim scientists today is how to find a comprehensive formulation of the various theories of knowledge that can be accepted by all people, so that Islamic science is not only free from the shadow of imperialism of Western epistemology, but is able to reflect in a concrete concept of Islam as ‘rahmatan lil ‘alamin’. This paper seeks to reorient the meaning of monotheism in the development epistemology of science which is featured with theocentric-humanism, that is, in addition to spiritual oriented (tawhid) it is also able to accommodate the interests of human beings (amal).Dalam konteks ilmu pengetahuan, upaya reformasi yang dilakukan oleh pemikir Muslim kontemporer sejauh ini belum mampu mengubah secara signifikan bayang-bayang kemajuan Barat. Kondisi ini disebabkan oleh efek pemikiran Barat yang dikemas dalam epistemologi mereka. Tentu saja, kita tidak bisa menyalahkan Barat karena mereka memiliki paradigma dan tolok ukur sendiri yang berbeda dengan paradigma Islam dalam mengembangkan ilmu pengetahuan. Dengan demikian, pertanyaan yang muncul, mengapa sarjana Muslim tidak bekerja keras untuk membangun sebuah epistemologi yang membawa pesan tauhid, mengapa mereka terburu-buru untuk menerima kebenaran epistemologi Barat tanpa melakukan telaah berdasar pada wahyu, sehingga mereka menjadi pengikut setia teori dan konsep Barat. Dengan demikian, tantangan terbesar bagi para ilmuwan Islam saat ini adalah bagaimana menemukan formulasi yang komprehensif dari berbagai teori pengetahuan yang bisa diterima oleh semua orang, sehingga ilmu Islam tidak hanya bebas dari bayang-bayang imperialisme epistemologi Barat, namun mampu secara total mencerminkan konsep yang konkret, tentamg Islam sebagai obor penerang (huda) yang dibawa oleh Rasulullah sebagai ‘rahmatan lil’ alamin’. Tulisan ini berusaha untuk melakukan re-oreintasi dan rethinking makna tauhid dalam perkembangan epistemologi ilmu pengetahuan yang ditampilkan bersamaan dengan aspek teosentris-humanisme, yaitu, selain berorientasi pada aspek spiritual (tauhid) juga mampu mengakomodasi kepentingan manusia (amal).